English Literature : A Very Short Introduction - Bate, Jonathan (Oxford Oxford University Press, 2010)
English Literature: A Very Short Introduction discusses why literature matters, how narrative works, and what is distinctly English about English literature. Jonathan Bate considers how we determine the content of the field, and looks at the three major kinds of imaginative literature - English poetry, English drama and The English novel.
Include Illustrations and Index.
A Very Short Introduction.
Keywords: English literature